2001
DOI: 10.1161/hc4301.097873
|View full text |Cite
|
Sign up to set email alerts
|

“Edge Effect” of 32 P Radioactive Stents Is Caused by the Combination of Chronic Stent Injury and Radioactive Dose Falloff

Abstract: Background-Radioactive stents have been reported to reduce in-stent neointimal thickening. An unexpected increase in neointimal response was observed, however, at the stent-to-artery transitions, the so-called "edge effect." To investigate the factors involved in this edge effect, we studied stents with 1 radioactive half and 1 regular nonradioactive half, thereby creating a midstent radioactive dose-falloff zone next to a nonradioactive stent-artery transition at one side and a radioactive stent-artery transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 42 publications
1
21
0
2
Order By: Relevance
“…6 The cause of the edge effect is not completely understood. The combination of dose falloff and stent injury has reproduced the edge effect with radioactive stents in animal models and in clinical trials, 7,8 but the relationships between edge effect and inadequate coverage of the injured segment by the radioactive source were never tested prospectively. The optimal margin coverage necessary to eliminate the edge effect, its consequences on nonstented segments, and the decremental effects of stenting after the brachytherapy procedure on the late outcome are unknown.…”
mentioning
confidence: 99%
“…6 The cause of the edge effect is not completely understood. The combination of dose falloff and stent injury has reproduced the edge effect with radioactive stents in animal models and in clinical trials, 7,8 but the relationships between edge effect and inadequate coverage of the injured segment by the radioactive source were never tested prospectively. The optimal margin coverage necessary to eliminate the edge effect, its consequences on nonstented segments, and the decremental effects of stenting after the brachytherapy procedure on the late outcome are unknown.…”
mentioning
confidence: 99%
“…This strongly suggested that the combination of low-dose radiation in association with chronic injury by the stent is the main determinant of neointimal hyperplasia. 10 Despite the prevention of the deleterious effects of negative remodeling seen at the stent edges in previous radioactive stent trials by the Cold Ends segments, a restenosis rate of 22% was observed. Therefore, Cold Ends stents did not resolve edge restenosis.…”
Section: Discussionmentioning
confidence: 98%
“…Figure 2-5 shows the tight stenosis at the stent edges, which are marked by arrows. This phenomenon has generally been observed 2 to 3 mm distal and proximal to the stent (Albeiro et al, 2000b;Serruys and Kay, 2000;van der Giessen et al, 2001). …”
Section: Edge Restenosis or "Candy Wrapper Effect"mentioning
confidence: 87%
“…It is hypothesized that decreased radiation doses at the edges of the stent might actually stimulate restenosis, while higher doses in the middle inhibit it (van der Giessen et al, 2001). Barotrauma at stent edges during the implantation procedure might be a factor as well.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation